1980
DOI: 10.1177/014662168000400209
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of the Nedelsky and Angoff Cutting Score Procedures Using Generalizability Theory

Abstract: The American College Testing Program Nedelsky (1954) and Angoff (1971) have suggested procedures for establishing a cutting score based on raters' judgments about the likely performance of minimally competent examinees on each item in a test. In this paper generalizability theory is used to characterize and quantify expected variance in cutting scores resulting from each procedure. Experimental test data are used to illustrate this approach and to compare the two procedures. Consideration is also given to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
96
2
2

Year Published

1982
1982
2015
2015

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(101 citation statements)
references
References 9 publications
1
96
2
2
Order By: Relevance
“…11,12 There is still no consensus as to the exact number of judges needed, and although previous studies have suggested a range of 5-20, most authors suggest that a group of 10 is an appropriate number. [16][17][18] Judges should also be knowledgeable of the curriculum that is being assessed, the abilities of the student cohort and should be ideally selected with a balanced mix of age, gender, educational experience and subject experience.…”
Section: ) Select Appropriate Judgesmentioning
confidence: 99%
“…11,12 There is still no consensus as to the exact number of judges needed, and although previous studies have suggested a range of 5-20, most authors suggest that a group of 10 is an appropriate number. [16][17][18] Judges should also be knowledgeable of the curriculum that is being assessed, the abilities of the student cohort and should be ideally selected with a balanced mix of age, gender, educational experience and subject experience.…”
Section: ) Select Appropriate Judgesmentioning
confidence: 99%
“…This method of analysis has been described as 'essentially variance components analysis viewed from the perspective of generalizability' (Brennan and Lockwood, 1980) and variance components for before and after discussion Shaded values indicate the probability that the borderline candidate would correctly answer items in each category. These values were derived internally through a series of pilot trials of the Ebel method.…”
Section: Reliabilitymentioning
confidence: 99%
“…This provides a measure of the error associated with the pass mark for the paper, and indicates how another set of judges would set the pass mark for the paper (by generalising across the sample of judges used). The variance of the item effect is omitted from the error variance (Brennan and Lockwood, 1980;Verhoeven et al, 1999), and the root mean squared error (RMSE) estimated as:…”
Section: Reliabilitymentioning
confidence: 99%
“…The Angoff method has been studied extensively (e.g. Brennan and Lockwood 1980;Livingston and Zieky 1989;Busch and Jaeger 1990;Chang 1999;Goodwin 1999;Giraud et al 2000;Hambleton 2001;MacCann 2008a). The Bookmark method is a newer method that is becoming very popular in the US and is attracting considerable research (e.g.…”
Section: Standard Settingmentioning
confidence: 99%